The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1020-49892004000500008
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa de aborto induzido: comparação entre duas metodologias

Abstract: The ballot box method was suitable for studying the frequency of induced abortion and for researching other topics that may lead to underreporting by the persons interviewed, especially in population-based samples. Rephrasing the ballot box method question about abortion (for example, eliminating the word "child") would probably increase the method's sensitivity, that is, its ability to detect induced abortions that had occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
0
14
0
7
Order By: Relevance
“…Studies that do not use techniques that guarantee secrecy tend to produce an underestimation of the magnitude of abortion [5][6][7][8][9][10][11] . For example, the National Health Survey of 2013 (2013 PNS), which was conducted by the Brazilian Institute of Geography and Statistics (IBGE), obtained data through face-to-face interviews with interviewers of both sexes and concluded that only 2.1% of women between the ages of 18 and 49 -a proportion significantly smaller than that of the 2010 PNA-had had an abortion 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies that do not use techniques that guarantee secrecy tend to produce an underestimation of the magnitude of abortion [5][6][7][8][9][10][11] . For example, the National Health Survey of 2013 (2013 PNS), which was conducted by the Brazilian Institute of Geography and Statistics (IBGE), obtained data through face-to-face interviews with interviewers of both sexes and concluded that only 2.1% of women between the ages of 18 and 49 -a proportion significantly smaller than that of the 2010 PNA-had had an abortion 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Destacam-se algumas investigações locais 7,8,9,10,11 , um estudo com escolares 12 e uma pesquisa multicêntrica, restrita à população de jovens 13 No primeiro, a entrevistada depositava, em urna, sua resposta à questão direta se já havia feito "um aborto de um filho", enquanto que no segundo, oralmente, respondia a questões feitas por entrevistadores sobre se já havia engravidado em condições em que não podia ou não queria, e o desfecho desta gravidez. Os autores obtiveram relato de aborto induzido de 3,8% aplicando as questões indiretas, elevando-se para 7,2% com o método da Urna.…”
Section: Os Estudos De Base Populacionalunclassified
“…Para atender cada um desses objetivos foram desenvolvidas diversas etapas de investigação. O detalhamento dos métodos para atingir o primeiro objetivo encontra-se em outra publicação 7 . No presente artigo, encontram-se especificados materiais e métodos utilizados para atingir o segundo objetivo.…”
Section: Metodologia Desenhounclassified